Changes in regional settlement systems in Poland - Runge Anna (Environmental & Socio-economic Studies, 2023)
This article is an attempt to identify regularities in changes in regional settlement systems in Poland with an indication of the elements that showed the highest population dynamics (growth or decline) in particular periods, thus contributing to changes in the structure of these systems. In order to show similarities and differences in the course of the analyzed changes, univariate statistical measures (median, quartiles) were used. This allowed for presenting a dynamic typology of these changes in order to show their cyclical nature and spatial diversity. The results show that these processes do not occur in a similar direction in all regions. The model of consistent changes in the size structure of cities concerns the settlement core of the country (Mazowieckie, Wielkopolskie, Małopolskie), while the resequential changes generally took place in the agricultural peripheries of the country (Podlaskie, Warmińsko-mazurskie), which were drained from the demographic potential by the migration outflow of the population the earliest, as well as in industrial regions (Śląskie, Łódzkie), where the political and economic transformation significantly affected population processes.